Depressive disorders in patients with duodenal ulcer in the acute and remission stages - Demydas, Olena (Psychosomatic Medicine and General Practice, 2023)
Abstract of the report "DEPRESSIVE DISORDERS IN PATIENTS WITH DUODENAL ULCER IN THE ACUTE AND REMISSION STAGES"